A Biblia és az európai integráció jogi alapjai a római jog közvetítésével: Bevezető - Hamza, Gábor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The European Integration is going back in centuries old spiritual traditions. The lawyers availed themselves to a considerable extent of the tenets of the Bible. Roman law (ius Romanum) served as a foundation for the 16th century legal humanism and was a goldmine for the rationalist natural law doctrines. In the 19th century, Roman law is molded in the spirit of legal positivism primarily through German Science of Pandects. Roman law is substantional material of the private law codices in Europe. It is obvious that the European integration needs both the harmonization and the unification in particular with regard to private law- related legislation. The realization legal harmonization could take the form of Council regulation, directive and also could be realized via coordinated national legislation. The members, for example of the Accademia dei giusprivatisti europei based on Pavia, among whom we can find experts of Roman law, English common law, and modern codified private law, in their efforts to codify the European law of contracts, view as their primary mission the creation of a compromise between Roman law, primarily based on codified continental private law, and contract constructions of English common law. The private law of the European countries is closely connected to Roman law. Taking into consideration the significant role of Roman law in the analysis of the evolution of European private law, regarding both the 27 member states of the European Union (Eu) and to those states being presently – yet – no member states of the Eu, is justified by spiritual traditions rooted in the tenets of the Bible.